Nghiên cứu cấu trúc của hai thiosemicacbazon và phức chất Ni(II) của chúng bằng phương pháp phổ khối lượng và cộng hưởng từ hạt nhân - Kính, Chu Đình; Độ, Vũ Đăng; Hồng Tuyết, Phan Thị (Vietnam Journal of Chemistry, 2014)
Octanal 4-phenyl thiosemicarbazone, citronellal thiosemicarbazone and their Nickel(II)’s complexes have been investigated by MS and NMR method. The structure of the thiosemicarbazones and complexes were established.